The Loss of Content in Contemporary Humanist and Philosophical Thought in the Development of the School of Critical Ontologism - ŽITKO, Pavao (Anafora, 2023)
The paper observes the crisis of the humanities through the prism of the current state of philosophical thought from the critical position of Italian ontologism. From a historical and scientific point of view, philosophy has long been considered as encompassing all human knowledge without a disciplinary division and consequent limitation to its specific domain. Today, philosophy is understood only as one of the scientific fields of humanistic declension. From the speculative point of view, philosophy has experienced the same evolutionary destiny of branching towards its own specifics, analogous to the progressive development of natural sciences and their cognitive penetration into the structures of reality. Philosophy has, therefore, experienced a systematic split as a discipline, depending on the argument of its research: philosophy of history, philosophy of mind, aesthetics, logic, ontology, philosophy of law, etc., thus losing sight of the fact that the speculative realm of philosophical thought is the only humanistic field in which the uniqueness of each specific argument of cognition is thought through. The only argument that unites all individual sciences is being as such, which the current philosophy hardly deals with at all.